Faktor Penyebab Anak Melakukan Tindak Pidana Kekerasan Fisik Yang Mengakibatkan Kematian - Sabihi, Abdul Rizky; Apripari, Apripari; Kaluku, Julisa Aprilia (CV. ITTC INDONESIA, 2023)
One of the crimes of physical violence was ever committed by a child until the victim died, as the child who committed physical violence resulted in the death of the victim. For the actions committed by the child as the perpetrator of the crime, the judge sentenced the child to 4 years in prison. The purpose of this research is to find out the factors that cause children to commit crimes of physical violence that result in death, criminal responsibility by children who commit physical violence that result in death, as well as the application of sanctions to children who commit crimes of physical violence that result in death. The type of research used is normative juridical research with a statutory approach and a case approach, which is supported by data obtained from library data including books, laws and regulations, and court decisions, and in this case the data is processed using qualitative analysis. Based on the results of the study, the factors that cause children to commit crimes of physical violence which result in death are due to several factors, both internal and external factors. Criminal liability by children who commit physical violence resulting in death can be seen from the provisions in Article 351 paragraph (3) of the Criminal Code, as the criminal responsibility is imposed on children when the child is proven to have fulfilled the criminal elements in the form of mistakes made by children, violence The physical violence that was done was done by the child, and the victims who were victims of physical violence were known to have died during or after the physical violence was carried out. The application of sanctions to children who commit acts of physical violence resulting in death, namely imposing prison sanctions on children, therefore, is sentenced to 4 years in prison.